Seed and Foliar Application of Amino Acids Improve Variables of Nitrogen Metabolism and Productivity in Soybean Crop - Teixeira, Walquíria F.; Fagan, Evandro B.; Soares, Luis H.; Soares, Jérssica N.; Reichardt, Klaus; Neto, Durval D. (Frontiers in Plant Science, 2018)
The application of amino acids in crops has been a common practice in recent years, although most of the time they are associated with products based on algae extracts or on fermented animal or vegetable wastes. However, little is known about the isolated effect of amino acids on the development of crops. Therefore, the objective of this research was to evaluate the effect of the application of isolated amino acids on the in some steps of the soybean nitrogen metabolism and on productivity. Experiments were carried out in a greenhouse and in the field with the application of the amino acids glutamate (Glu), phenylalanine (Phe), cysteine (Cys) and glycine (Gly) and as a set (Glu+Phe+Cys+Gly), as seed treatment (ST), as foliar application (FA) and both (ST+FA), at the V4 growth stage. Evaluations consisted of nitrate reductase and urease activities, nitrate, ureide, total amino acids and total nitrogen content in leaves, and productivity. The application of Glu to leaves, Cys as ST and a mixture of Glu+Cys+Phe+Gly as ST+FA in the greenhouse experiment increased the total amino acids content. In the field experiment all treatments increased the amino acid content in leaves. At the V6 stage in the field experiment, all modes of Gly application, Glu as ST and FA, Cys and Phe as ST+FA and Glu+Cys+Phe+Gly as FA increased the nitrate content in leaves. In the greenhouse, application of Cys and Phe as ST increased the production of soybean plants by at least 21%. The isolated application of Cys, Phe, Gly, Glu and the set of these amino acids as ST increased the productivity of soybean plants in the field experiment by at least 22%.